Development and Evaluation of Trans-Resveratrol-Loaded Transfersomes: Role of Cholesterol in Formulation Design for Dermal Delivery - Sarotsumpan P; Chiu IH; Wu PC; Khong NMH; Liew CV; Chutoprapat R (Nanotechnology, Science and Applications)
Pattarakamol Sarotsumpan,1 I-Hui Chiu,2 Pao-Chu Wu,2 Nicholas Mun Hoe Khong,3 Celine Valeria Liew,3 Romchat Chutoprapat1 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmaceutical Sciences, Chulalongkorn University, Bangkok, Thailand; 2School of Pharmacy, Kaohsiung Medical University, Kaohsiung, Taiwan; 3School of Pharmacy, Monash University Malaysia, Subang Jaya, Selangor, MalaysiaCorrespondence: Romchat Chutoprapat, Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmaceutical Sciences, Chulalongkorn University, Bangkok, 10330, Thailand, Email romchat.c@pharm.chula.ac.thPurpose: This study investigated the development and characterization of trans-resveratrol-loaded transfersomes, with and without cholesterol, for potential non-irritating dermal applications.Methods: Transfersomes were prepared using thin-film hydration combined with probe sonication, incorporating hydrogenated lecithin, cholesterol, and Tween® 60 in six different ratios. The formulations were characterized for their physicochemical properties, including particle size, polydispersity index, zeta potential, entrapment efficiency, morphology, in vitro release profiles, dermal permeation potential, and safety profile.Results: All formulations exhibited particle sizes below 150 nm and zeta potentials below − 30 mV, indicating favorable characteristics for dermal delivery. Cholesterol incorporation significantly increased particle size and enhanced zeta potential (p< 0.05). Formulations containing 3– 3.5% w/v hydrogenated lecithin achieved superior entrapment efficiency (> 90%) compared to those with lower lecithin content (p< 0.05), regardless of cholesterol incorporation. Transfersomes containing cholesterol displayed morphology with well-defined edges compared to cholesterol-free formulations. In vitro release studies revealed distinct release profiles, with cholesterol-free formulations releasing 70– 83% of trans-resveratrol over 24 hours, compared to only 0– 30% for cholesterol-containing formulations. Strat-M® membrane-based permeation studies confirmed enhanced trans-resveratrol delivery across all transfersomal systems compared to the saturated solution (p< 0.05), though cholesterol showed no significant impact on permeation efficiency. These findings indicate that cholesterol influences release profile but has limited effect on permeation efficiency. Safety assessment using the Hen’s Egg Test-Chorioallantoic Membrane (HET-CAM) assay classified the developed transfersomes as weak irritants, indicating their dermal safety. Notably, formulation F3, with a hydrogenated lecithin to cholesterol to Tween 60 ratio of 6:0:4, emerged as the optimal candidate, achieving the highest release rate (80.24% over 24 hours) while maintaining favorable permeation compared to control.Conclusion: These findings feature the potential of transfersomal systems, particularly cholesterol-free variants, as promising carriers for the effective and safe dermal delivery of trans-resveratrol. Keywords: trans-resveratrol, transfersomes, cholesterol, in vitro release, in vitro permeation, HET-CAM test